Machine type communication using LTE for electrical health monitoring system - Heng, Nien Leng (2019)
As the technologies advance, there is a significant enhancement in machineries. It is unlikely for existing system architectures to interpret and troubleshoot the fault error on its own due to the increase of complexity. To prevent any machine failures, there is a need to implement electrical health monitoring system. One of the implementations is to store information of the machineries to a cloud service platform to monitor and analyse the potential problems to avoid any machinery failure. Therefore, this paper aims to provide the development on how data, mainly analog to digital converter (ADC) signals, can be transmitted to a cloud service platform by using Machine Type Communication (MTC) system. MTC is a form of data communication that enables a broad range of applications. To spread these applications widely, cellular systems are considered as a potential candidate to provide connectivity for these MTC devices. With the help of Internet of Things (IoT), it reduces to the probability of facing problems associated with bottlenecks, breakdown and system damages. It allows physical devices to stay connected and communicate actively, which generate an exceptional quality control through the internet.